Do foreign workers reduce trade barriers? Microeconomic evidence - Andrews, Martyn; Schank, Thorsten; Upward, Richard (Wiley, 2017)
This paper provides evidence that foreign workers reduce firms' trade costs and thus increase the probability that firms export. This informs both the literature on trade costs and the microeconomic literature on firms' export behaviour. We identify the nationality of each worker in a large sample of German establishments, and relate this to the exporting behaviour of these establishments. We allow for the possible endogeneity of an establishment's workforce by instrumenting the share of foreign workers with the regional distribution of foreign workers in the wider labour market. We find a significant effect of worker nationality on exporting which is not driven by the industrial, occupational or locational concentration of migrants. The effect is much stronger for senior occupations, who are more likely to have a role in exporting decisions by the establishment. The relationship is also stronger when we consider exports to particular regions and workers from these regions, consistent with a gravity model in which trade flows from country i to j are a function of migrants from j in i.